A New Conatus for the New World: Dewey’s Response to Perfectionist Conceptions of Democratic Education - Özel, Jasmin; Beisecker, David; Ervin, Joe (Conatus - Journal of Philosophy, 2021)
We argue for a reconsideration of the claim that Spinoza’s perfectionist conception of education was ushering in a form of radical humanism distinctly favorable to democratic ideals. With the rise of democratic societies and the corresponding need to constitute educational institutions within those societies, a more thoroughgoing commitment to democratic social ideals arose, first and foremost in American educational thought. This commitment can be seen especially in Dewey’s philosophy of education. Specifically, Dewey and Spinoza had strikingly distinct conceptions of the overall aims of schooling. While Spinoza takes the aim of education to be the perfection of a student’s original nature, Dewey takes education to involve the collective acquisition of an additional nature, reflecting the norms and expectations of one’s specific community. In this paper, we juxtapose these two distinct conceptions of education alongside one another, with an eye towards illuminating the limitations of a perfectionist theory of education for the individual, as we find it in Spinoza, within a democratic society.